PEMBELAJARAN KIMIA MODEL THINK-PAIR-SHARE DAN NUMBERED HEADS TOGETHER DITINJAU DARI KEMAMPUAN AWAL DAN AKTIVITAS BELAJAR (Jurnal Inovasi Pendidikan Kimia, 2012)
Tujuan penelitian ini adalah untuk mengetahui: (1) Pengaruh pembelajaran kimia model TPS (Think-Pair-Share) dan NHT (Numbered Heads Together) terhadap prestasi belajar siswa. (2) Pengaruh kemampuan awal tinggi dan rendah terhadap prestasi belajar siswa. (3) Pengaruh aktivitas belajar tinggi dan rendah terhadap prestasi belajar siswa. (4) lnteraksi antara pembelajaran kimia model TPS dan NHT dengan kemampuan awal. (5) lnteraksi antara pembelajaran kimia model TPS dan NHT dengan aktivitas belajar siswa. (6) lnteraksi antara kemampuan awal siswa dengan aktivitas belajar siswa. (7) lnteraksi antara pembelajaran kimia model TPS dan NHT dengan kemampuan awal siswa dan aktivitas belajar siswa. Penelitian ini menggunakan metode eksperimen. Berdasarkan hasil penelitian dapat disimpulkan: (1) Tidak ada pengaruh pembelajaran kimia model TPS dan NHT terhc!'.:::r; prestasi belajar siswa. (2) Ada pengaruh kemampuan awal tinggi dan rendah terhadap prestasi belajar siswa. (3) Ada pengaruh aktivitas belajar tinggi dan rendah terhadap prestasi belajar siswa. (4) Ada interaksi antara pembelajaran kimia model TPS dan NHT dengan kemampuan awal. (5) Tidak ada interaksi antara pembelajaran kimia model TPS dan NHT dengan aktivitas belajar siswa. (6) Tidak ada interaksi antara kemampuan awal siswa dengan aktivitas belajar siswa. (7) Tidak ada interaksi antara pembelajaran kimia model TPS dan NHT dengan kemampuan awal siswa dan aktivitas belajar siswa.The aims of this research were to find out: (1) the effect of Chemistry Learning using TPS (Think-Pair Share) and NHT (Numbered Heads Together) Models toward student's achievement. (2) the effect of high and low prior knowledge toward student's achievement. (3) the effect of high and low student's activity toward their achievement. (4) the interaction between Chemistry Learning Models with prior knowledge toward student's achievement. (5) the interaction between Chemistry Learning Models with student's activity toward student's achievement. (6) the interaction between student's prior knowledge and student's activity toward student's achievement. (7) the interaction between Chemistry Learning Models, student's prior knowledge and student's activity toward student's achievement. The research used experimental method. Based on the results of the research can be concluded that: (1) there was no effects of chemistry learning models to the student's achievement. (2) there was an effect of high and low prior knowledge to the student's achievement. (3) there was an effect of high and low student's activity toward student's achievement. (4) there was interactions between chemistry learning models and prior knowledge toward student's achievement. (5) there was no interactions between chemistry learning models and the student's activity toward student's achievement. (6) there was no interactions between prior knowledge and the student's activity toward student's achievement. (7) there was no interactions between chemistry learning models, prior knowledge and the student's activity toward student's achievement.